2012
DOI: 10.5625/lar.2012.28.1.17
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effects of topical application ofAloe vera,thyroid hormoneandsilver sulfadiazineon skin wounds inWistarrats

Abstract: Many research studies report the healing effects of Aloe Vera, thyroid hormone cream and silver sulfadiazine. However, the effects of these therapeutic agents are not well understood and have not been compared in one study. This study aimed at investigating the effects of topical application of an Aloe vera gel, a thyroid hormone cream and a silver sulfadiazine cream on the healing of skin wounds surgically induced in Wistar rats for determining the treatment of choice. In a randomized controlled trial, twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…The results indicated that Aloe vera was significantly more effective in wound healing as attested by tensile stress parameters in sutured incisions [23]. However, to provide more evidence for our previous study, we applied a histological approach to examine and compare the effects of topical application of AV, TC and SSD cream on the healing process of sutured skin incision in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that Aloe vera was significantly more effective in wound healing as attested by tensile stress parameters in sutured incisions [23]. However, to provide more evidence for our previous study, we applied a histological approach to examine and compare the effects of topical application of AV, TC and SSD cream on the healing process of sutured skin incision in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…vera, known as "the healing plant" (Choi et al, 2001), is effective during healing processes in various tissues. Its effect is described in the literature for fibroblast proliferation, angiogenesis, production of different growth factors, synthesis of ECM components, such as hyaluronic acid, dermatan sulfate and collagen, and increased amount of crosslinks between the collagen molecules, in skin, bone fractures and gastric lesion (Chithra et al, 1998a,b,c;Somboonwong et al, 2000;Rodríguez et al, 2002;Eamlamnam et al, 2006;Prabjone et al, 2006;Habeeb et al, 2007;Takahashi et al, 2009;Takzare et al, 2009;Atiba et al, 2011;Tarameshloo et al, 2012). According to the results of Maia Filho et al (2010), A. vera phonophoresis was effective for the treatment of tendinitis, with reduction of edema and number of inflammatory cells, as well as promoting the recovery of the tensile strength of tendon.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies suggest that topical Aloe vera improves wound healing, 24 has antipsoriatic activity comparable with tazarotene (0Á1%) in a mouse model, 25 may protect skin against carcinogens 26 and shows activity in a variety of dermatological conditions, 27 but reviews of RCTs of Aloe vera products for wound healing have been inconclusive. 28 Experimental studies on indirubin and its derivatives indicate antiproliferative effects in epidermal keratinocytes, 29 antiinflammatory activities, 30 radioprotective effects 31 and effects on regulatory T cells.…”
Section: Experimental Studies On These Plantsmentioning
confidence: 99%